Gelae parile - Majka, Christopher; Langor, David (Zenodo, 2008)
Gelae parile (Fall, 1934) NEWFOUNDLAND: Spruce Brook, 9.VII.1949, E. Palmen, (2, MZHF). NOVA SCOTIA: Inverness Co.: Lone Shieling, Cape Breton Highlands National Park, vii.1983, R. Vockeroth, malaise trap, (2, CNC); MacKenzies Mtn., Cape Breton Highlands National Park, 11-18.VII.1983, R. Vockeroth, pan trap, (2, CNC); Queens Co.: Medway River, 13.VII.1993, J and T. Cook, car net, (2, JCC). Gelae parile is newly recorded in Newfoundland, Nova Scotia, and in Atlantic Canada as a whole (Fig. 7). It was collected in hemlock, pine, aspen, fir, maple, and other forests from a variety of litter sources such as rotting stumps, and leaf litter. There are host records from the slime molds Cribraria sp. and Dictydium cancellatum (Batch) McBride (Miller and Wheeler 2004). : Published as part of Majka, Christopher & Langor, David, 2008, The Leiodidae (Coleoptera) of Atlantic Canada: new records, faunal composition, and zoogeography, pp. 357-402 in ZooKeys 2 (2) on page 382, DOI: 10.3897/zookeys.2.56, http://zenodo.org/record/576397 : {"references": ["Miller KB, Wheeler QD (2004) Two new genera of Agathidiini from the Nearctic and Neotropical regions (Coleoptera: Leiodidae). The Coleopterists Bulletin 58 (4): 466 - 487."]}